P022: Physician reporting of medically unfit drivers: barriers and incentives. (15th May 2017) - Brubacher, J.R.; Renschler, C.; Gomez, A.M.; Huang, B.; Lee, W.C.; Erdelyi, S.; Chan, H.; Purssell, R.
Abstract : Introduction: Most medically unfit drivers are not reported to licensing authorities. In BC, physicians are only obligated to report unfit drivers who continue to drive after being warned to stop. This study investigates barriers to and incentives for physician reporting of medically unfit drivers.Methods: We used an online survey to study physician-reported barriers to reporting medically unfit drivers and their idea of incentives that would improve reporting. Email invitations to participate in the survey were sent to all physicians in BC through DoctorsofBC and to all emergency physicians (EPs) in the UBC Department of Emergency Medicine.Results: We received responses from 242 physicians (47% EPs, 40% GPs, 13% others). The most common barrier to reporting was not knowing which unfit drivers continue to drive (79% of respondents). Other barriers included lack of time (51%), lack of knowledge of the process, guidelines, or legal requirement for reporting (51%, 50%, 45% respectively), fearing loss of rapport with patients (48%), pressure from patients not to report (34%), lack of remuneration (27%), and pressure from family members not to report (25%).EPs were significantly less likely than other physicians to cite loss of rapport, pressure from patients, or pressure from family as barriers, but more likely to cite not being aware of drivers who continue to drive after being warned, lack of knowledge (regarding legal requirements to report, guidelines for determining fitness, and the reporting process), and lack of time. Factors that would increase reporting unfit drivers included better understanding of criteria for fitness to drive (70%), more information regarding how to report (67%), more information on when to report (65%), and compensation (43%).Free text comments from respondents identified other barriers/incentives. Reporting might be simplified by telephone hotlines or allowing physician designates to report. Physicians feared legal liability and suggested the need for better medico-legal protection. Loss of patient rapport might be minimized by public education. Failure of response from licensing authorities to a report (long wait times, lack of feedback to physician) was seen as a barrier to reporting.Conclusion: We identified barriers to physician reporting of medically unfit drivers and incentives that might increase reporting. This information could inform programs aiming to improve reporting of unfit drivers.